2021
DOI: 10.1002/tcr.202100240
|View full text |Cite
|
Sign up to set email alerts
|

Ortho C−H Functionalization of 2‐Arylimidazo[1,2‐a]pyridines

Abstract: C−H activation and functionalization is quite promising in recent days as the strategy offers a go‐to general method for different bond formations and hence grants synthetic versatility. At the same time, imidazopyridine, a fused bicycle of imidazole moiety with pyridine ring, has a profound impact due to its ubiquitous and prodigious application in medicinal as well as material chemistry. The presence of N‐1 atom in 2‐arylImidazo[1,2‐a]pyridine facilitates the coordination with metal catalysts leading to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…Our group added several developments on indazole chemistry [17] as well as C−H functionalization strategy [18] . In addition to that, last year, we have also reported a review on ortho C−H functionalization of an elegant heterocycle, 2‐arylImidazo[1,2‐ a ]pyridine [19] . Therefore, in continuous efforts on the development of indazole chemistry as well as C−H functionalization strategy, herein, we wish to report the first review on ortho C−H functionalization of 2‐arylindazoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group added several developments on indazole chemistry [17] as well as C−H functionalization strategy [18] . In addition to that, last year, we have also reported a review on ortho C−H functionalization of an elegant heterocycle, 2‐arylImidazo[1,2‐ a ]pyridine [19] . Therefore, in continuous efforts on the development of indazole chemistry as well as C−H functionalization strategy, herein, we wish to report the first review on ortho C−H functionalization of 2‐arylindazoles.…”
Section: Introductionmentioning
confidence: 99%
“…[18] In addition to that, last year, we have also reported a review on ortho CÀ H functionalization of an elegant heterocycle, 2-arylImidazo[1,2-a]pyridine. [19] Therefore, in continuous efforts on the development of indazole chemistry as well as CÀ H functionalization strategy, herein, we wish to report the first review on ortho CÀ H functionalization of 2-arylindazoles. In the course of this review, we have divided the article based on the type of functionalization for simplification and a better understanding of the reader.…”
Section: Introductionmentioning
confidence: 99%
“…Our group also contributed significantly to the C–H functionalization strategy 18 and different heterocyclic chemistry. 19 In addition to that, we have reported reviews on the ortho C–H functionalization of 2-arylimidazopyridine 20 and 2-aryl-2 H -indazole. 21 Therefore, in continuation of our efforts in quinoxaline chemistry as well as the ortho C–H functionalization strategy, we wish to report herein the first literature review on the ortho C–H bond functionalization of 2-arylquinoxalines.…”
Section: Introductionmentioning
confidence: 99%
“…The C3 position of imidazo[1,2- a ]pyridine is susceptible to radical reactions under transition metal catalysis, 27 and C–H activation and functionalization reactions via concerted metalation-deprotonation or electrophilic substitution pathways. 28 Excellent reviews by Konwar, 28 Hajra, 29 Mahdavi, 30 and Lianyang 31 have covered different aspects of the functionalization of imidazopyridines in the last two decades. The imidazo-moiety of imidazo[1,2- a ]pyridines may also act as a metal coordinating directing group in functionalization reactions of 2-arylimidazo[1,2- a ]pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…The imidazo-moiety of imidazo[1,2- a ]pyridines may also act as a metal coordinating directing group in functionalization reactions of 2-arylimidazo[1,2- a ]pyridine. 29 To give a few examples regarding chelation-assisted functionalizations: Patel's research group demonstrated a solvent-controlled regiodivergent Mn-catalyzed alkylation of imidazo[1,2- a ]pyridine with maleimide. 32 Wang et al successfully executed a domino arylation reaction of 2-arylimidazo[1,2- a ]pyridines under Pd-catalysis.…”
Section: Introductionmentioning
confidence: 99%